Understanding the antecedents of workplace happiness - Salsabila, Andilita Zahra; Febrianti, R. Adjeng Mariana (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to understand the factors that are predictors of workplace happiness felt by individuals, by looking at the effect of work climate, perceived supervisor support, and perceived organizational support. The research was conducted quantitatively by giving questionnaires to the respondents, namely 185 employees of private companies in the city of Bandung, West Java. The data obtained were then processed using Structural Equation Modeling with SPSS 25 software. The research findings indicate that work climate, perceived supervisor support, and perceived organizational support have a positive effect on workplace happiness, either partially or simultaneously. This research also provides implications and suggestions for future researchers and practitioners in organizations.